0608 Characterization of Sleep in Emerging Adults with Cystic Fibrosis on CFTR Modulator Therapy. (25th May 2022) - Meltzer, Lisa; Jump, Stephanie; Gross, Jane
Abstract: Introduction: Sleep disturbances are common among youth and adults with cystic fibrosis (CF). However, few CF programs regularly screen for sleep disorders beyond sleep disordered breathing. Emerging adults (18 to 25 years) with CF are a unique population, experiencing changes in sleep and life transitions (e.g., education, work, relationships), while also managing a complex chronic illness. CF transmembrane regulator (CFTR) modulator therapies have significantly improved medical and quality of life outcomes, yet the impact on sleep remains to be determined. Methods: Emerging adults with CF (EA-CF; n=22, 59.1% female) and without CF (EA-Control; n=17, 76.5% female) completed an online survey that queried (1) symptoms of restless legs syndrome, parasomnias, and daytime sleepiness, and (2) frequency of exogenous sleep aid use (i.e., prescription medications, melatonin, over-the-counter [OTC] sleep aids, and marijuana/CBD). EA-CF were also asked about perceived changes in falling asleep, night waking frequency and duration, and daytime sleepiness since starting CFTR modulator therapy. Results: Sleep disorder symptoms were more frequently reported by EA-CF compared to EA-Control, including restless legs syndrome (31.8% vs. 23.5%, small effect size), parasomnias (40.9% vs. 29.4%, small effect size), and excessive daytime sleepiness/fatigue (50.0% vs. 23.5%, medium effect size). OTC sleep aid use did not differ by group (EA-CF 31.8% vs. EA-Control 35.3%), but the frequency was significantly greater in EA-CF (>once/month: EA-CF 27.3% vs. EA-Control 0%, <once/month: EA-CF 4.5% vs. EA-Control 35.3%, large effect size). More EA-CF reported CBD/marijuana use compared to EA-Control (36.4% vs. 17.6%, small effect size), with 31.8% of EA-CF reporting use of CBD/marijuana at least several nights a week (vs. 5.9% of EA-Control, small effect size). Since starting CFTR modulatory therapy, 27.3% of EA-CF reported falling asleep faster, 31.8% reported fewer night wakings, 36.4% reported shorter night wakings, and 36.4% reported reduced daytime sleepiness. Conclusion: This study is one of the first to examine sleep in emerging adults with CF on CFTR modulator therapy, with results highlighting the importance of screening for sleep disorders other than sleep disordered breathing, use of exogenous sleep aids to facilitate sleep, and the benefits of CFTR modulator therapy on sleep. Data collection is ongoing. Support (If Any): Natalie V. Zucker Award